اللجان والهيئات الإدارية المناط بها تصنيف و تهيئة مناطق الكتل الجبلية في القانون الجزائري Commitees And Administrative Bodies In Charge Of The Management And The Classification Of Mountain Zones Under Algerian Law. - جمال, قتال; مرسلي, عبد الحق (Université de M'sila, 2019)
اخذ المشرع الجزائري ضمن اهتماماته تنظيم الكتل الجبلية في الجزائر من خلال إصداره لعدة قوانين و مراسيم بموجبها صنف الكتل الجبلية و حددها، و انشأ لها لجان وهيئات وطنية تعمل على تهيئتها و تنميتها، حيث انشأ المجلس الوطني للجبل، صندوق الجبل، اللجنة الوزارية المشتركة لدراسة تصنيف المناطق الجبلية،اللجنة الوزارية المشتركة لفحص أنظمة تهيئة إقليم الكتل الجبلية، و من خلال هذه الدراسة حاولنا بالتحليل ان نعطي دور كل هيئة و مهامها في هذا المجال من خلال تحليل نصوص القوانين و المراسيم التي جاء بها المشرع Abstract: The algerian legislator has among his aims the organization of the mountains through the odoption of several laws and decrees by which the mountains are classified and limited and for this objectif the algerian law establishes some national bodies and commitees charged to develop and to manage this specific zones. In this context he created the national council for mountain, the mountain fund and the common ministry commitee for the classification of mountains. In addition to the common ministry commitee for the examination of the mointain zones management systems. By this papier we try to analyze the role of each body and commitee , and its fonctions in this field, by the examination of laws and rules
Keywords: الجبل، تنمية المناطق الجبلية، تصنيف الكتل الجبلية. ; mountain, mountain zones development, mountain classification